Monitoring and control of AC power distribution board through sound card-based SCADA system - Jabir, Muhammad (2014)
The concept of wide-area monitoring of each and every aspect of the electrical distribution system, its control and protection is the basic demand of this era. This is because of the electrical power demand is growing much faster which demands the more energy generating system like renewable sources which are cheap and easily available even at close to load and result complex electrical generating system. For safe and control electrical power from these complex electrical generating system to industrial and most important loads like telecommunication site load, the electrical energy is provide to system through AC power distribution board which pass electrical energy from these generating sources i.e. TNB and other sources like generator and renewable to load in control way. The present AC power distribution board can monitor and control only current and voltages of the coming electrical energy sources. Also there is no remote monitoring system that can check the coming AC power status even of voltage and current. The monitoring of voltage and current can monitor only by volt and ammeter that are presents on the AC power distribution boards (ACPDB). This thesis explored the challenges and feasibility of the implementation of real-time system analysis features in order to monitor and control the AC electrical power distribution board (ACPDB) of the telecommunication sites. By using the sound card based SCADA system the signal of maximum range 2.1V that is get from potential and current transformers of the electrical system of telecommunication site has sent to computer or process device which integrates with the LabVIEW software. Sound card is the most cheapest and easily integrate to computer as data acquisition device rather than other acquisition cards which are expensive as well as demand separate software and software license in order to integrate hardware to computer software. LabVIEW is the one of the latest and efficient software that easily integrate with hardware by using sound card and receives the ACPDB signal with proper generated code. In this thesis ACPDB of type V4 has been used for monitoring and control. For V4 ACPDB the single phase voltage can measure upto 380V and current can measure up to 140A by using sound card SCADA. The LabVIEW with the created design code electrical power distributed system of telecommunication site is monitored and controlled. Using sound card based SCADA system we are able to monitor any kind of aspect from fundamental quantity to distortion analysis. The values of monitored system store in the storage devices which are helpful for load forecasting and able to manage electrical sources. The protection of ACPDB is achieved by setting reference values in LabVIEW and LabVIEW send control signal to hardware in the event of fault.